The encampment of the English forces near Portsmouth, together with a... - James Basire (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: The encampment of the English forces near Portsmouth, together with a view of the English and French fleets at the commencement of the action between them on the XIXst of July MDXLV. The Cowdray engraving of the battle of the Solent, 1545. The encampment of the English forces near Portsmouth, together with a view of the English and French fleets at the commencement of the action between them on the XIXst of July MDXLV, by James Basire, engraved from a coeval painting, at Cowdray in Sussex, the Seat of Lord Viscount Montague. The Cowdray engravings are a set of images recording Henry VIIIs campaign in France during the summer of 1544 and the events of 19th July 1545 in Portsmouth, the Solent and the Isle of Wight, showing the attempt by the forces of the French King, Francis 1st, to invade England and wrest the crown from Henry. One of the most notable events that occurred during the Battle of the Solent was the loss of King Henry VIIIs vice flagship, the Mary Rose, and her sinking is clearly shown in this picture.
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; tableau; Iconographie